POLA KOMUNIKASI ORANG TUA DAN ANAK DI ERA DIGITAL: ANALISIS QURANIC PARENTING TERHADAP Q.S YUSUF [12]:4-6 - Muhammad Fajri (IAT IAIN Pontianak, 2022)
Abstract This paper talks about the analysis of Qur'anic parenting in Q. S Yusuf: 4-6 and its relation to the communication patterns of parents and children in the digital era. The results of this study show that in today's digital era, many parents use communication patterns laissez-faire, where parents rarely interact with children, because of the impact of the full freedom given to children in using gadgets that result in parental relationships and children often experience miscommunication. Therefore, it is necessary to imitate the communication patterns applied by Yusuf and Ya'qub which use interpersonal communication patterns with an interactive model, which means that there is an open attitude, mutual trust and emotional closeness between Yusuf and his father, Ya'qub. This is evidenced by Yusuf call to his father who uses the pronunciation